Resposta da irrigação suplementar em diferentes cenários para a cultura da soja na microrregião de Passo Fundo, RS. - Vivan, Gisele Aparecida (2010)
The management of water in agriculture should offer advantages to producers in the use of water, increasing crop productivity, reduced costs of production, enhancing their sustainable use. In this focus, this paper aims to quantify the additional irrigation required by the soybean crop in the microregion of Passo Fundo. Simulating combinations of sowing dates and duration of the crop cycle, determining the scenario with higher probability of application of smaller irrigation, also studying the effect in terms of yield of applying different rates of irrigation. The study was based on the agricultural years 93/94 to 06/07, using the model WINISAREG to determine the supplemental irrigation. Performing analysis of variance and comparison test of means for the interpretation and determination of the combination of sowing date and duration of crop cycle that has become more favorable in terms of reduced need for supplemental irrigation. Was used also functions of yield to the study of the effect of varying of the blade on the additional yield for the soybean crop. It was noted that all scenarios demonstrated need for additional water, with application requirements for water ranging from 54.1 to 429.9 mm, and the cultures with life cycle middle and late seeding in 15/12 required smaller blades supplemental irrigation compared to other combinations simulated. The functions of income in relation to irrigation depth showed maximum yield reductions between 25-42%, depending on the scenario studied. Concludes that the distribution of rainfall is high variable in space and time, verifying necessity of applying additional irrigation, regardless of the sowing date and the simulated scenario, being the yield on culture, most affected as lower the percentage of supplemental irrigation applied.